The ATC/TTC haplotype in the Interleukin 8 gene in response to Gram-negative bacteria: A pilot study - Pigossi, Suzane C. [UNESP]; Anovazzi, Giovana [UNESP]; Finoti, Livia S. [UNESP]; de Medeiros, Marcell C. [UNESP]; de Souza-Moreira, Tatiana Maria [UNESP]; Mayer, Marcia P.A.; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP]; Rossa Junior, Carlos [UNESP]; Scarel-Caminaga, Raquel M. [UNESP] (Elsevier, 2019)
Objective: The aim of this study was to investigate the functionality of ATC/TTC (Hap-1) and ATT/TTC (Hap-2) Interleukin (IL) 8 gene haplotypes in the response of neutrophils to Gram-negative bacteria associated with periodontitis. Design: Neutrophils were isolated by gradient centrifugation from whole peripheral blood of systemically healthy individuals presenting the two IL8 gene haplotypes. Neutrophils were stimulated with P. gingivalis, A. actinomycetemcomitans and PMA/ionomycin. Cytokine gene expression (RT-qPCR) and migration/chemotaxis (boyden chamber assay) were compared according to the presence of Hap-1 or Hap-2 haplotypes. Protein production was also evaluted in the multiplex assay using the mixed population of leukocytes present in the whole blood from the same individuals. The influence of these two haplotypes on the IL8 promoter activity was assessed in gene-reporter experiments. Results: Hap-1 haplotype in neutrophils and leukocytes exacerbated the response to stimulation with Gram-negative bacteria, with higher levels of TNF-α (mRNA and protein), IL-1β, IL-2R and IFN-γ (protein) and with increased chemotaxis. Presence of the T allele at the rs4071 polymorphism (alias -251) was associated with increased activity of IL8 proximal promoter. Conclusions: Neutrophils and leukocytes carrying the Hap-1 haplotype (ATC/TTC) in the IL8 gene present an enhanced response to stimulation with Gram-negative bacteria associated with periodontitis. Presence of the T allele (rs4073) in the IL8 proximal promoter increases transcription activity.
Keywords: Gram-negative bacteria; Interleukin-8; Leukocytes; Neutrophils; Polymorphism functionality